Nutritional studies on Lotus corniculatus containing condensed tannins to increase reproductive rate and lamb growth under commercial dryland farming conditions : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University, Palmerston North, New Zealand - Ramírez-Restrepo, Carlos Alberto (Massey University, 2004)
Five rotational grazing experiments were carried out at Massey University's Riverside farm, in the Wairarapa, on the East Coast of the Southern North Island, New Zealand, to compare the effects of feeding Lotus corniculatus L. (birdsfoot trefoil; cv. Grasslands Goldie) or perennial ryegrass (Lolium perenne)/white clover (Trifolium repens) dominant pasture upon sheep year round productivity. These studies also investigated under grazing, seasonal and annual net herbage accumulation rate and seasonal dynamics of undisturbed (i.e. non-grazed) net herbage accumulation rate of L. corniculatus relative to that of grass-dominant pasture. Aspects of in vivo digestibility of dry matter (DMD), organic matter (OMD), digestible organic matter in the dry matter (DOMD) and metabolisable energy (ME) concentration of L. corniculatus at different stages of maturity over the spring, summer and autumn were investigated in three indoor digestion trials. 1. Two field experiments (Chapter 2) were conducted during spring to assess the effects of grazing mixed age undrenched ewes on L. corniculatus (n = 50) or pasture (n = 50) and their lambs (mainly twins) on live weight (LW), wool production, faecal nematode egg count (FEC) and dag score. In Experiment 1 (18 October 2000 to 21 January 2001) and Experiment 2 (3 October 2001 to 2 January 2002) both forages were fed ad libitum. Total condensed tannin (CT) concentration in the diet selected was 24 to 27 g CT/kg DM for L. corniculatus and 1.4 to 1.5 g CT/kg DM for pasture. The LW gain, weaning LW and wool production were consistently greater (P < 0.001) for lambs grazing L. corniculatus, in either Experiment 1 (258 vs. 189 g/day; 36.1 vs. 30.1kg; 1.17 vs. 0.98 kg) and in Experiment 2 (247 vs. 162 g/day; 31.8 vs. 24.1kg; 1.17 vs. 0.81 kg), respectively. Ewe and lamb dag scores were strongly and positively correlated with dag weight (P < 0.001) and generally increased with time in sheep grazing pasture, whilst grazing on L. corniculatus consistently reduced dag score. FEC in ewes grazing pasture showed a post-parturient rise (PPR) following lambing, whilst ewes grazing L. corniculatus had a reduced PPR in FEC. Up to day 70, FEC in lambs grazing L. corniculatus was lower than that for lambs grazing pasture, but between day 70 and the end of both experiments (approximately day 90), FEC in lambs grazing L. corniculatus increased to similar values as for pasture-fed lambs. FEC was not correlated with dag score or dag weight in ewes or lambs grazing pasture, but these indices were weakly and positively correlated in ewes and lambs grazing L. corniculatus, suggesting that lowering FEC on L. corniculatus also reduced dag formation. It was concluded that under dryland farming conditions, the use of L. corniculatus during the spring/early summer lactation period can increase lamb LW and wool production, whilst eliminating the need for pre-lambing anthelmintic drenching and probably reducing the amount of insecticide needed to control flystrike. These effects compared to pasture are probably due to higher digestibilty, higher ME concentration, higher voluntary feed intake (VFI), and to the effect of CT in reducing rumen protein degradability and controlling internal parasites in sheep grazing L. corniculatus. The absence of endophyte in L. corniculatus may have also have contributed to these effects. 2. During 2001 and 2002 (Chapter 3), grazing trials from February to November were conducted for 279 days (Experiments 1) and 285 days (Experiment 2), to compare the effects of grazing shorn mixed age Romney ewes in light condition on L. corniculatus versus pasture during the mating period (9 weeks, Experiment 1) and 11 weeks (Experiment 2). In Experiment 2, the length of time (days) that ewes need to graze L. corniculatus before mating to maximise reproductive performance was also investigated. Common objectives in both Experiments were to measure forage feeding effects on ewe wool production and LW of their lambs at weaning. In Experiment 1, groups of ewes (n = 100) were fed on either L. corniculatus or pasture at a herbage allowance of 1.8 kg green DM/ewe/day for the first three weeks of feeding and increased to ad libitum (2.3 kg green DM/ewe/day) during the mating period for two cycles. In Experiment 2, groups of 75 ewes grazed L. corniculatus for 42, 21, 10 and 0 days before a synchronised oestrus, with pasture being grazed for the balance of the 42 days. All L. corniculatus groups continued grazing L. corniculatus for a further 5 weeks. Feed allowance was initially 2.0 kg green DM/ewe/day, increased to 2.3 kg green DM/ewe/day during the mating period over the two cycles. At the end of L. corniculatus feeding in both experiments the groups were combined and grazed on pasture until weaning. Total CT concentration in the diet selected was 18 to 29 g CT/kg DM for L. corniculatus, with only trace amounts in pasture. In Experiment 1 mating ewes on L. corniculatus compared to pasture increased number of lambs born and lambs weaned per ewe lambing by 16 and 32% units respectively (P < 0.05), due to more multiple and less single births (P = 0.06) and to reduced lamb mortality (P < 0.05) between birth and weaning. In Experiment 2, increasing the numbers of days of grazing L. corniculatus before ovulation (0, 10, 21, 42 days) linearly increased ovulation rate (P < 0.05), lambs born and lamb weaned by up to 16% units, but had no effect upon lamb mortality. Mating ewes on L. corniculatus increased wool production (P < 0.01) and fibre length (P < 0.05) in Experiment 1 but not in Experiment 2. Grazing L. corniculatus had no effect on lamb birth weight and only small positive effects on weaning LW. It was concluded that, under commercial dryland farming conditions, the use of L. corniculatus during the mating season in late summer/autumn can be used to increase reproductive efficiency and wool production, with the largest responses in years with exceptionally dry autumn periods. These effects are probably due to the higher digestibility and ME concentration of L. corniculatus than pasture and to the CT in L. corniculatus reducing rumen protein degradability and leading to greater essential amino acid (EAA) absorption from the small intestine. Effects of forage CT upon the uterine microenvironment at the time of conception, implantation and early foetal growth, need to be investigated in future studies. It is also suggested that effects of mating on L. corniculatus upon lamb mortality between birth and weaning should be further investigated with ewe numbers/treatment increased from 100 to 350. 3. During the summer of 2002/2003, another grazing trial (Chapter 4: 95 days) compared the effects of grazing L. corniculatus and pasture on LW and the dynamics of nematode parasite infection in Suffolk x Romney weaned lambs fed ad libitum. Half of the lambs (n = 30) grazing either L. corniculatus or pasture received oral anthelmintic at the start and at monthly intervals (regular-drenched groups), whilst the remaining 30 lambs in each treatment only received oral anthelmintic when mean faecal nematode egg counts (FECs) exceed 1,000 eggs/g wet faeces (trigger-drenched groups), which occurred on day 58 only for both groups. Trigger and regular-drench lambs grazed separate areas. Total CT concentration in the diet selected was 40 to 31 g CT/kg DM for L. corniculatus, with only trace amounts in pasture. Regular-drenched lambs grazing L. corniculatus had significantly higher LW gain (298 g/day) and carcass weight gain (133 g/day) than all the other groups, whilst trigger-drenched lambs grazing L. corniculatus had significantly greater LW gain (228 g/day) and carcass gain (99 g/day) than regular-drenched (200; 66 g/day) and trigger-drenched (187; 63 g/day) lambs grazing pasture. Carcass fatness was significantly lower for trigger-drenched lambs than for regular-drenched lambs, when fed either L. corniculatus or pasture. Dag score was consistently lower for regular-drenched lambs grazing L. corniculatus than pasture; trigger-drenched lambs showed similar effects up to day 48, with no differences between the two groups thereafter. Regular anthelmintic treatment maintained FECs at low values, while parasitised lambs on L. corniculatus tended to have higher FECs than pasture-fed lambs. Relative to trigger-drenched lambs that grazed pasture, grazing trigger-drenched lambs on L. corniculatus had significantly reduced worm burdens of Haemochus contortus, Teladosargia spp., Nematodirus spp. and Cooperia spp. at slaughter, but greater burdens of Trichostrongylus spp., Chabertia ovina, Oesophagostonum spp. and Trichuris ovis were present in L. corniculatus-fed lambs. It was concluded that grazing L. corniculatus under dryland farming conditions compared to pasture can increase LW gain of weaned lambs, whilst reducing reliance on anthelmintic drenches to control parasites. These effects are probably due to increased protein supply from the action of CT enabling the lambs to have a higher LW gain when carrying a parasite burden, and to L. corniculatus better maintaining its high ME value under drought conditions. Using L. corniculatus to finish weaned lambs without anthelmintic drenches for a seven-week period is proposed. 4. A three-year study (Chapter 5; November 2000 to October 2003) was conducted to compare, under grazing conditions, seasonal and annual grazed net herbage accumulation rate and seasonal dynamics of undisturbed (i.e. non-grazed) net herbage accumulation rate of L. corniculatus relative to grass-dominant pasture. Prediction equations to estimate standing DM in L. corniculatus and pasture from the rising plate meter (RPM) and sward surface height were also generated. L. corniculatus and pasture growing in a moderate fertility and low-pH soil (pH 5.35) accumulated similar total herbage masses (24.3 vs. 24.1 t DM/ha) over the 3-year period, with the DM production being greater for L. corniculatus than for pasture during 2000-2001, producing more DM during summer/autumn drought conditions. The net herbage accumulation rate from undisturbed areas of L. corniculatus and pasture were similar in spring, summer and autumn. Seasonal variation in the calibration regressions fitted to estimate herbage mass of L. corniculatus non-destructively, suggested a combination of destructive and nondestructive methods are needed to assess herbage mass. It was concluded that L. corniculatus has the potential to increase the performance of a pasture-based sheep dryland farming system due to its ability to grow in acidic soils, its tolerance of drought conditions during summer/autumn and its seasonality of feed supply. 5. Three digestion experiments involving cryptorchid weaned lambs were conducted for 14 days over the spring, summer and autumn to determine changes in in vivo digestibility of DM, OM, digestible OM in the DM and ME concentration of L. corniculatus at different stages of maturity. In vivo digestibility samples were then used as standards to investigate if the enzymatic in vitro system of Roughan and Holland (1977) could predict OMD and DOMD of CT-containing L. corniculatus. Digestibility of L. corniculatus declined as it matured, but the rate of decline was much less than occurs for temperate grasses and for white clover. It was concluded that the in vitro enzymatic system of Roughan and Holland (1977) can be used to predict OMD and DOMD of L. corniculatus, provided a standard curve involving in vivo data generated with L. corniculatus is used. Using a standard curve with in vivo data from pasture led to bias which increased at lower OMD values. Reasons for the consistent differences between L. corniculatus and pasture standard curves are discussed, including possible effects of residual bound CT in lowering in vitro digestibility. From this series of experiments, this study is the first to report that relative to conventional perennial ryegrass/white clover, mating ewes on L. corniculatus under grazing conditions may reduce post-natal lamb mortality. It is also the first study to show that grazing sheep on L. corniculatus can maintain productivity during spring and summer with reduced dependence on anthelmintic drench input. It is concluded that whole farm modelling, mechanical harvesting and conservation strategies, selection of L. corniculatus germplasm for creeping-type plants more suited to grazing and the integration of new crops containing secondary compounds, such as chicory, should be considered to support major advances in sustainable dryland sheep farming systems.
Keywords: Lotus corniculatus; Sheep; Lambs; Feeding and feeds; Feed utilisation efficiency; Reproduction; Growth; New Zealand; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300400 Animal Production::300403 Animal nutrition